Protocol for the isolation and single-nuclei multiomic analyses of the human fetal epicardium - Stanislao Igor Travisano; Ching-Ling Lien (STAR Protocols, 2024)
Summary: The characterization of cell populations that reside in the outer layer of the heart has been hindered by difficulties in their isolation. Here, we present a protocol for isolation and single-nuclei multiomic analyses of the human fetal epicardium. We describe steps for microdissection, isolation, and enrichment of epicardial cells by mechanical dissociations and direct lysis. We then detail procedures for integrating transcriptome and chromatin accessibility datasets. This approach allows the analysis of diverse cell populations, marked by unique cis-regulatory elements.For complete details on the use and execution of this protocol, please refer to Travisano et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.